Comprehensive Analysis of Colorectal Cancer Immunity and Identification of Immune-Related Prognostic Targets. (30th March 2022) - Wen, Huijuan; Li, Fazhan; Bukhari, Ihtisham; Mi, Yang; Guo, Chenxu; Liu, Bin; Zheng, Pengyuan; Liu, Simeng
Abstract : Colorectal cancer (COAD) is ranked as the third most common cancer and second in terms of cancer-related deaths worldwide. Due to its poor overall survival and prognosis, the incidents of COAD are significantly increasing. Although treatment methods have greatly been improved in the last decade, it is still not good enough to have satisfactory treatment outcomes. In recent years, immunotherapy has been successful to some extent in the treatment of many cancers but still, many patients do not respond to immunotherapy. Therefore, it is essential to have a deeper understanding of the immune characteristics of the tumor microenvironment and identify meaningful immune targets. In terms of immune targets, COAD has been poorly explored; thus, in the current study, based on the immune cell infiltration score and differentially expressed genes, COAD tumors were classified into hot and cold tumors. The Least Absolute Shrinkage and Selection Operator (LASSO) regression analysis was used to identify hub genes, construct a prognostic model, and screen potential immune targets. In total, 12 genes ( CLK3, CYSLTR2, GJA10, CYP4Z1, FAM185A, LINC00324, EEF1A1P34, EEF1B2P8, PTCSC3, MIR6780A, LINC01666, and RNU6.661P ) differentially expressed between hot and cold tumors were screened out. Among them, CYSLTR2 was considered as a potential candidate gene, because it showed a significant positive correlation with immune cell infiltration and immune checkpoints ( PDCD1, CD274, and CTLA4 ). Finally, we constructed and validated a new prognostic model for COAD showing 0.854 AUC for the ROC curve, and these results provide sufficient potential to choose CYSLTR2 as an important immune target for the prognosis of COAD.